Corticosterone Enhances the AMPK-Mediated Immunosuppressive Phenotype of Testicular Macrophages During Uropathogenic Escherichia coli Induced Orchitis - Zhang, Zhengguo; Jiang, Ziming; Zhang, Yiming; Zhang, Yu; Yan, Yan; Bhushan, Sudhanshu; Meinhardt, Andreas; Qin, Zhihai; Wang, Ming (Frontiers in Immunology, 2020)
Abstract: Testicular macrophages (TM) play a central role in maintaining testicular immune privilege and protecting spermatogenesis. Recent studies showed that their immunosuppressive properties are maintained by corticosterone in the testicular interstitial fluid, but the underlying molecular mechanisms are unknown. In this study, we treated mouse bone marrow-derived macrophages (BMDM) with corticosterone（50 ng/ml） and uncovered AMP-activated protein kinase (AMPK) activation as a critical event in M2 polarization at the phenotypic, metabolic and cytokine production level. Primary TM exhibited remarkably similar metabolic and phenotypic features to corticosterone-treated BMDM, which were partially reversed by AMPK-inhibition. In a murine model of uropathogenic E. coli-elicited orchitis intraperitoneal injection with corticosterone increased the percentage of M2 TM in vivo, in a partially AMPK-dependent manner. This study integrates the influence of corticosterone on M2 macrophage metabolic pathways, phenotype and function, and highlights a promising new avenue for the development of innovative therapeutics for orchitis patients.